Clinical outcome data of chronic pain patients treated with cannabis-based oils and dried flower from the UK Medical Cannabis Registry. (3rd April 2023) - Tait, James; Erridge, Simon; Holvey, Carl; Coomber, Ross; Usmani, Azfer; Sajad, Mohammed; Hoare, Jonathan; Khan, Shaheen; Weatherall, Mark; Rucker, James J; Platt, Michael; Sodergren, Mikael H
ABSTRACT: Background: The following study evaluated the clinical outcomes of patients enrolled in the UK Medical Cannabis Registry, who were treated with inhaled dried flower (Adven® EMT2, Curaleaf International, Guernsey), and sublingual/oral medium-chain triglyceride-based oils (Adven, Curaleaf International, Guernsey) for chronic pain. Methods: In this cohort study, the primary outcomes were changes in validated patient reported outcome measures (PROMs) at 1, 3, and 6 months compared to baseline, and adverse event analysis. Statistical significance was defined as p  < 0.050. Results: Three hundred and forty-eight (45.7%), 36 (4.7%), and 377 (49.5%) patients were treated with oils, dried flower, or both, respectively. Patients treated with oils or combination therapy recorded improvements within health-related quality of life, pain, and sleep-specific PROMs at 1, 3, and 6 months ( p  < 0.050). Patients treated with combination therapy recorded improvements in anxiety-specific PROMs at 1, 3, and 6 months ( p  < 0.050). 1, 273 (167.3%) adverse events were recorded, with previously cannabis naïve users, ex-cannabis users, and females more likely to experience adverse events ( p  < 0.050). Conclusions: This study observed an association between initiation of CBMP treatment and improved outcomes for chronic pain patients. Prior cannabis use and gender were associated with adverse event incidence. Placebo-controlled trials are still necessary to establish the efficacy and safety of CBMPs for chronic pain.